Penerapan Metode Pembelajaran Berbasis Proyek untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa di SDN Cibentar II - mufita, rina; sariatin, imas (Papanda Publisher, 2022)
This study delves into the positive impact of implementing project-based learning methods on students' creative thinking skills at SDN Cibentar 2. Adopting a qualitative approach, the research involved participatory observation, in-depth interviews with teachers and students, and data analysis. The research findings indicate a significant improvement in student participation, collaboration skills, and problem-solving abilities. The theoretical analysis underscores the alignment of this method with constructivism and active learning approaches, providing a robust theoretical foundation for the observed positive outcomes. Practical implications of this research include recommendations to expand the integration of project-based learning methods in the curriculum and encourage students to design their own projects. The research conclusion emphasizes the positive achievements and provides a basis for continuous improvement in creative learning at the elementary school level. By highlighting the success of implementing project-based learning methods, this study offers insightful and relevant perspectives for the development of teaching practices at the elementary level. Subsequent research could explore the long-term impact of implementing these methods and involve more stakeholders.